Kapitalisme Indonesia: Langkah-Langkah Tanpa Peta - Musyaddad, A. (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Gadjah Mada, 2003)
As the thurst of the current global capitalist order, neoliberalism has been philosopically suffer from a serious flaws_ Having presents the flaws, this article then demonstrates practical implication of the current attempt of liberalization in Indonesia. Not only capitalism has never been whole materialized in Indonesia, its brings Indonesia to uncertain direction. The attempt to minimize the role of the state has brought about serious fragmentation and it in turn opened up conflict over political-economic resources.